Development and Validation of the Early Life Dynamics and Narcissism scale: Exploring Family Dynamics and Parenting styles for Understanding Narcissistic traits in Men - Babar, Maham; Shakil, Muneeba (Annals of Human and Social Sciences, 2025)
This research’s focus was to develop and validate “The Early Life Dynamics and Narcissism Scale” (ELDNS). A culturally sensitive therapeutic screening tool, designed to identify impacts of early life dynamics and parenting styles on Narcissistic tendencies in men. The study was done in five phases that included semi structured interviews leading to a preliminary set of 29 items refined by expert evaluation, followed by a pilot study, explanatory factor analysis and psychometric testing of the scale. Factor analysis identified two principal factors: “Childhood familial dynamics and adverse experiences “and “Parental influence and emotional outcomes”. The scale exhibited good internal consistency and temporal stability. Moreover, evaluations of convergent and divergent validity demonstrated the scale’s precision. This tool would have great clinical implications. More research should be conducted to explore if this scale is applicable in the different cultural settings to enhance the robustness of the scale.